Effects of the therapy shift from cortisone acetate to modified-release hydrocortisone in a group of patients with adrenal insufficiency - Frigerio, Sofia; Carosi, Giulia; Ferrante, Emanuele; Sala, Elisa; Polledri, Elisa; Fustinoni, Silvia; Ambrosi, Bruno; Chiodini, Iacopo; Mantovani, Giovanna; Morelli, Valentina; Arosio, Maura (Frontiers in Endocrinology, 2023)
Objective: patients with adrenal insufficiency (AI) may be exposed to supraphysiological glucocorticoids levels during standard treatment with cortisone acetate (CA) or immediate-release hydrocortisone (IR-HC). Recent studies, predominantly including patients in IR-HC treatment, suggested that modified-release hydrocortisone (MRH) provide a more physiological cortisol rhythm, improving metabolic control and quality of life. Our primary aim was to assess clinical and biochemical modifications in patients shifted from CA to MRH. Design/Methods: we designed a retrospective longitudinal study, enrolling 45 AI patients (22 primary and 23 secondary AI) treated exclusively with CA thrice daily, shifted to MRH once daily; 29/45 patients concluded at least 18-months follow-up (MRH-group). We recruited 35 AI patients continuing CA as a control group (CA-group). Biochemical and clinical data, including metabolic parameters, bone quality, and symptoms of under- or overtreatment were collected. In 24 patients, a daily salivary cortisol curve (SCC) performed before and one month after shifting to MRH was compared to healthy subjects (HS). Results: no significant changes in glycometabolic and bone parameters were observed both in MRH and CA-groups during a median follow-up of 35 months. A more frequent decrease in blood pressure values (23.1% vs 2.8%, p=0.04) and improvement of under- or overtreatment symptoms were observed in MRH vs CA-group. The SCC showed a significant steroid overexposure in both CA and MRH-groups compared to HS [AUC (area under the curve) = 74.4±38.1 nmol×hr/L and 94.6±62.5 nmol×hr/L respectively, vs 44.1±8.4 nmol×hr/L, p<0.01 for both comparisons], although SCC profile was more similar to HS in MRH-group. Conclusions: in our experience, patients shifted from CA to equivalent doses of MRH do not show significant glycometabolic modifications but blood pressure control and symptoms of over-or undertreatment may improve. The lack of amelioration in glucose metabolism and total cortisol daily exposure could suggest the need for a dose reduction when shifting from CA to MRH, due to their different pharmacokinetics.